Changing University Students’ Mindset: From Job Seekers to Job Creators - Hartono, Hartono (Technium Social Sciences Journal, 2021)
The government continues to encourage the growth of entrepreneurship in Indonesia. Currently, university graduates are generally more interested in becoming workers or employees than in creating jobs. Indonesia still needs around 4.75 million entrepreneurs. Data from the Ministry of Education and Culture shows that in general, college graduates are more interested in becoming job seekers than job creators. Therefore, universities have the responsibility to change the students’ mindset from wanting to become job seekers to job creators. This research is a qualitative study using the phenomenological approach. Data collection was carried out by means of semi structured interviews by selecting 20 students from private universities in Jakarta. The results of this study indicate that students’ mindset from job seekers to job creators cannot change without improvement of entrepreneurship education at universities. The students’ mindset must be changed from a fixed mindset to a growth mindset. Curricula and learning methods that are too theoretical must be transformed into learning that emphasizes practical elements and entrepreneurial mental development